Strategi Pemasaran Produk Kecantikan: Peran Celebrity Endorser dan Viral Marketing dalam Meningkatkan Minat Beli Scarlett Whitening - Tessa Anatasia; Lucia Sutiono; Bong Kim Sin; Shahnaz Khumaira; Syarifah Yustin (Syntax Corporation Indonesia, 2024)
This study aims to examine the impact of celebrity endorsers and viral marketing on purchase interest in Scarlett Whitening beauty products, focusing on the beauty community in Singkawang City. Using a quantitative approach, data was collected through questionnaires distributed to a purposive sample of 100 customers and consumers. The independent variables are celebrity endorsers and viral marketing, while the dependent variable is purchase interest. T-test results reveal that both celebrity endorsers and viral marketing significantly influence purchase interest individually. Additionally, F-test results confirm that these factors collectively have a significant simultaneous effect on purchase interest in Scarlett Whitening beauty products in Singkawang City.